Technical solution and application of 5G slicing private network based on cloud-network integration - Kai CHEN (Dianxin kexue)
Facing the diversified and personalized business needs of vertical industries, 5G network slicing can provide customized, secure, and intelligent services.Combined with OTN, IPRAN/STN resources, cloud resources, cloud-network integration, and fixed-mobile integration system capabilities, 5G network slicing enables customer terminals, wireless base stations, bearers, cores and intranet service platforms communicate through private network isolation channels.The architecture scheme and key technologies of the 5G end-to-end private slicing network were introduced, the difficulties encountered in the automatic opening of private slicing networks under the new-generation operating system was analyzed, and solutions was proposed, which would promote operators from traffic management to resource management era.